Diversité floristique et caractérisation structurale de la réserve forestière de Ouoghi en zone soudanoguinéenne (Centre-Bénin) - Ahouandjinou, Sfich T. B.; Yédomonhan, Hounnankpon; Tossou, Monique G.; Adomou, Aristide C.; Akoègninou, Akpovi (European Scientific Journal, ESJ, 2017)
Objective: The objective of this study is to identify the plant species and to characterize the vegetation of the Ouoghi forest reserve in the commune of Savè (Center-Benin). Method and results: Floristic and forest inventories were carried out through 144 relevés in according to the Braun-Blanquet method. A total of 246 plant species were identified. They belong to 178 genera and 63 families. Multivariate analyzes with the Community Analysis Package (CAP) software made it possible to individualize 3 vegetation formations comprising 8 plant groups. This is the shrub savannah with Prosopis africana and Pennisetum polystachion, the tree savannah with Hymenocardia acida and Pennisetum polystachion, the tree savannah to Vitellaria paradoxa and Pennisetum polystachion, the tree savannah to Pterocarpus erinaceus and Hyptis suaveolens, the woodland savannah with Daniellia Oliveri and Chromolaena odorata, the woodland savannah at Isoberlinia doka and Pennisetum polystachion, the woodland savannah at Daniellia oliveri and Andropogon tectorum and the tree flood savannah to Daniellia oliveri and Leersia hexandra. The floristic and structural parameters change from one group to another. Thus, the specific richness varies from 49 to 153 species and the diversity of families is between 22 and 49 with a predominance of Leguminosae. The density varies from 95 to 275 stems / ha, basal area from 2.35 to 8.44 m² / ha. Conclusion and application of results: The study evaluated the floristic diversity of the Ouoghi reserve. In addition, it indicated the need for its integral protection for its dynamics towards dry dense forest vegetation. Sustainable management of this site needs implication of local population.